The link between menin and pleiotrophin in the tumor biology of pancreatic neuroendocrine neoplasms - He, Liping; Boulant, Steeve; Stanifer, Megan; Guo, Cuncai; Nießen, Anna; Chen, Mingyi; Felix, Klaus M.; Bergmann, Frank; Strobel, Oliver; Schimmack, Simon (Cancer science, 2022)
MEN1, which encodes menin protein, is the most frequently mutated gene in pancreatic neuroendocrine neoplasms (pNEN). Pleiotrophin (PTN) has been reported as a downstream factor of menin that promotes metastasis in different tumor entities. In this study, the effect of menin and its link to PTN were assessed using features of pNEN cells and the outcome of patients with pNEN. The expression levels of menin and PTN in tissues from patients with pNEN were examined using qRT-PCR and western blot and compared with their metastasis status. Functional assays, including transwell migration/invasion and scratch wound-healing assays, were performed on specifically designed CRISPR/Cas9-mediated MEN1-knockout (MEN1-KO) pNEN cell lines (BON1MEN1-KO and QGP1MEN1-KO) to study the metastasis of pNEN. Among 30 patients with menin-negative pNEN, 21 revealed a strong protein expression of PTN. This combination was associated with metastasis and shorter disease-free survival. Accordingly, in BON1MEN1-KO and QGP1MEN1-KO cells, PTN protein expression was positively associated with enhanced cell migration and invasion, which could be reversed using PTN silencing. PTN is a predicting factor of metastatic behavior of menin-deficient-pNEN. In vitro, menin is able to both promote and suppress the metastasis of pNEN by regulating PTN expression depending on the tumoral origin of pNEN cells.